2009
DOI: 10.1523/jneurosci.5019-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

At Immature Mossy-Fiber–CA3 Synapses, Correlated Presynaptic and Postsynaptic Activity Persistently Enhances GABA Release and Network Excitability via BDNF and cAMP-Dependent PKA

Abstract: In the adult rat hippocampus, the axons of granule cells in the dentate gyrus, the mossy fibers (MF), form excitatory glutamatergic synapses with CA3 principal cells. In neonates, MF release into their targets mainly GABA, which at this developmental stage is depolarizing. Here we tested the hypothesis that, at immature MF-CA3 synapses, correlated presynaptic [single fiber-evoked GABA A -mediated postsynaptic potentials (GPSPs)] and postsynaptic activity (back propagating action potentials) may exert a critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
91
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 65 publications
(106 reference statements)
6
91
0
Order By: Relevance
“…In agreement with previous studies (Gutiérrez et al, 2003;Kasyanov et al, 2004;Safiulina et al, 2006;Safiulina and Cherubini, 2009;Sivakumaran et al, 2009), during the first week of postnatal life, minimal stimulation of granule cells in the dentate gyrus elicited lowprobability GPSCs, which were completely blocked by bicuculline (10 M) or picrotoxin (100 M). Depolarizing the cell to positive potentials (ϩ40 mV) produced bicuculline-sensitive outward currents with latency, onset, and deactivation kinetics similar to those obtained at Ϫ70 mV, further indicating that they were mediated by GABA A receptors (data not shown) (Safiulina et al, 2006).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with previous studies (Gutiérrez et al, 2003;Kasyanov et al, 2004;Safiulina et al, 2006;Safiulina and Cherubini, 2009;Sivakumaran et al, 2009), during the first week of postnatal life, minimal stimulation of granule cells in the dentate gyrus elicited lowprobability GPSCs, which were completely blocked by bicuculline (10 M) or picrotoxin (100 M). Depolarizing the cell to positive potentials (ϩ40 mV) produced bicuculline-sensitive outward currents with latency, onset, and deactivation kinetics similar to those obtained at Ϫ70 mV, further indicating that they were mediated by GABA A receptors (data not shown) (Safiulina et al, 2006).…”
Section: Resultssupporting
confidence: 92%
“…In six cases, stimulation of granule cells in the dentate gyrus failed to produce any synaptic response to the first stimulus (over at least 30 consecutive trials). However, occasional responses to the second stimulus suggested that these synapses were "presynaptically" silent (Gasparini et al, 2000;Kasyanov et al, 2004;Safiulina and Cherubini, 2009;Sivakumaran et al, 2009). Application of UBP 302 to "presynaptically" silent cells induced the appearance of synaptic responses to the first stimulus (supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study published in The Journal of Neuroscience, Sivakumaran et al (2009) elegantly explored the presence of STDP at hippocampal Mf-CA3 pyramidal cell synapses. They examined this issue during an early postnatal period (postnatal day 2-5) when these synapses are thought to operate mainly through depolarizing GABA A synaptic currents (Safiulina et al, 2006).…”
mentioning
confidence: 99%
“…Mechanistically, Sivakumaran et al (2009) found that STDP-LTP of GPSCs depended on postsynaptic calcium rise, postsynaptic protein kinase A (PKA) activity, and TrkB [brain-derived neurotrophic factor (BDNF) receptor] receptor activation. The authors hypothesize that the pairing protocol induced an activitydependent release of BDNF from CA3 pyramidal cells, which in turn acted presynaptically at mossy fiber terminals to increase probability of release.…”
mentioning
confidence: 99%